Energy research in developing countries - Graham, Stephen, 1946-; International Development Research Centre (Canada); Energy Research Group (Canada) (Ottawa : International Development Research Centre, 1994)
A one-volume summary of the 14 vols. of research reviews coordinated by the Energy Research Group.
"The Energy Research Group was a joint project of the International Development Research Centre and the United Nations University."--Introduction.
Includes bibliographical references (p. 299-306).
Keywords: Power resources -- Research -- Developing countries; Energy policy -- Developing countries